A CONTRIBUIÇÃO DO HANDEBOL PARA A FORMAÇÃO SOCIAL E EDUCAÇÃO DE JOVENS DA EQUIPE DO CAIC BALDUINO BARBOSA DE DEUS - Carla Pereira, Diana; Soares Alcântara de Sousa, Dheane; Calacio Silva, Eliclecio; Luiz Galan Ribeiro, Sérgio (Revista Form@re - Parfor/UFPI, 2026)
.